The Effectiveness Of Interactive Comic Media In Science Courses - Sri Utamingsih; Rani Susanti; Nur Fajrie; Khamdun Khamdun (Postgraduate, University of Mataram, 2023)
An innovative approach that has attracted attention in recent years is the use of interactive media, such as interactive comics, in the teaching of science. This study aims to analyze the effectiveness of interactive comic media for science subjects in fifth grade elementary school. This research belongs to the type of Research and Development (R&D) research with research and development procedures consisting of two stages: media development and media testing. The method used develop and test learning media uses the Borg and Gall model. The product trial design used a pretest posttest control group design on students at SDN 2 Jambu as the experimental class and students at SDN 11 Jambu as the control class. Data were collected by observation, questionnaires, tests, interviews and documentation. The statistical test of effectiveness was carried out with SPSS. Data on the effectiveness of interactive comics learning media were analyzed by gain test, t test at a significance level of 0.05. Learning media developed in the form of interactive comics. The interactive comic was developed based on a needs analysis conducted on fifth grade students and teachers in three elementary schools in the Mlonggo sub-district, Jepara Regency. The use of interactive comics is effective as evidenced by an increase in learning outcomes. The average percentage of prettest in the control and experimental classes is almost the same, namely 30.00 and 30.67. After being given the intervention, the average posttest of the control and experimental classes increased to 50.00 and 74.83. The results of the t test obtained that the value of t count = 8.803 with a significance level of 0.000 < = 0.05. The conclusion obtained is that the development of interactive comic media has proven to be effective for use in learning in the fifth grade of elementary school. It is recommended that teachers use interactive comics in learning because it can improve student learning outcomes